A Critical Review on the Standardization and Quality Assessment of Nonfunctional Laboratory Tests Frequently Used to Identify Inborn Errors of Immunity - Perazzio, Sandro Félix; Palmeira, Patricia; Moraes-Vasconcelos, Dewton; Rangel-Santos, Andréia; de Oliveira, João Bosco; Andrade, Luis Eduardo Coelho; Carneiro-Sampaio, Magda (Frontiers in Immunology, 2021)
Inborn errors of immunity (IEI), which were previously termed primary immunodeficiency diseases, represent a large and growing heterogeneous group of diseases that are mostly monogenic. In addition to increased susceptibility to infections, other clinical phenotypes have recently been associated with IEI, such as autoimmune disorders, severe allergies, autoinflammatory disorders, benign lymphoproliferative diseases, and malignant manifestations. The IUIS 2019 classification comprises 430 distinct defects that, although rare individually, represent a group affecting a significant number of patients, with an overall prevalence of 1:1,200-2,000 in the general population. Early IEI diagnosis is critical for appropriate therapy and genetic counseling, however, this process is deeply dependent on accurate laboratory tests. Despite the striking importance of laboratory data for clinical immunologists, several IEI-relevant immunoassays still lack standardization, including standardized protocols, reference materials, and external quality assessment programs. Moreover, well-established reference values mostly remain to be determined, especially for early ages, when the most severe conditions manifest and diagnosis is critical for patient survival. In this series, we intend to approach the issue of standardization and quality control of the nonfunctional diagnostic tests used for IEI, focusing on those frequently utilized in clinical practice. Herein, we will focus on discussing the issues of nonfunctional immunoassays (flow cytometry, enzyme-linked immunosorbent assays, and turbidimetry/nephelometry, among others), as defined by the pure quantification of proteins or cell subsets without cell activation or cell culture-based methods.